2011
DOI: 10.1016/j.jcrs.2010.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Automated keratometry in routine cataract surgery: Comparison of Scheimpflug and conventional values

Abstract: Overall, the equivalent K at 4.5 mm had the closest match with the conventional K values. The degree of interdevice variability with the conventional keratometer was lowest for the equivalent K at 4.5 mm and 5.0 mm, although this variability would be sufficient to influence intraocular lens power selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…Many studies 4,7,9,[24][25][26] have compared astigmatism magnitudes (K values) without taking the astigmatism meridian into account and in general found good agreement of measurements obtained by automated keratometry, manual keratometry, corneal topography, and Scheimpflug imaging. However, some studies found significant differences between devices.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies 4,7,9,[24][25][26] have compared astigmatism magnitudes (K values) without taking the astigmatism meridian into account and in general found good agreement of measurements obtained by automated keratometry, manual keratometry, corneal topography, and Scheimpflug imaging. However, some studies found significant differences between devices.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have been performed to compare corneal astigmatism measurements obtained with different keratometers, [3][4][5] Placido-disk videokeratoscopes, [6][7][8] and Scheimpflug imagers. 6,8,9 However, in general, these studies compared astigmatism magnitudes only, with no regard to the astigmatism meridian. Because astigmatism is a vector with a magnitude and a direction, vector analysis must be used to compare astigmatism data.…”
mentioning
confidence: 99%
“…Another group recently found a difference of -0.033 mm (equal to 0.19 D), also regarding the steep meridian [8]. Studies based on the former version of Pentacam or Pentacam HR also indicated differences in keratometric measurements [19][20][21][22][23][24]. Karunaratne found statistically significant differences between the mean keratometric values of the IOL Master and Pentacam equivalent keratometry readings at 2-, 3-and 4.5-mm zone measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as the gold standard in evaluation of new instruments, including the Lenstar device (HaagStreit) and the Pentacam device (Oculus) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%